Peran Faktor Demografi Dalam Memoderasi Pengaruh Gaya Hidup Terhadap Niat Beli Buah Segar Pada Moena Fresh Bali Di Kota Denpasar - Ardiawan, I Komang Feri; Kusumadewi, Ni Made Wulandari (E-Jurnal Manajemen, 2015)
This study was conducted to determine the effect of education and income levels in moderat ing influence of lifestyle on the intention to buy fresh fruit in Moena Fresh Bali. This research was conducted in the city of Denpasar, samples taken as many as 119 people with purposive sampling method. Data was collected by distributing questionnaires using a 5-point Likert scale to measure 17 indicators. The analysis technique used is moderated regression analysis. Results of these studies show that lifestyle affects the purchase intentions of fresh fruit in Moena Fresh Bali, education level moderate the influence on the intention to buy fresh fruit in Moena Fresh Bali, income levels moderate the influence of lifestyle on the intention to buy fresh fruit in Moena Fresh Bali. This shows that demographic variables are able to moderate the influence of lifestyle on the intention to buy fresh fruit in Moena Fresh Bali.
Keywords: Niat Beli; Gaya Hidup; Tingkat Pendidikan; Tingkat Pendapatan